2017
DOI: 10.1080/0284186x.2017.1355113
|View full text |Cite
|
Sign up to set email alerts
|

Impact of model and dose uncertainty on model-based selection of oropharyngeal cancer patients for proton therapy

Abstract: Model and dose uncertainty highly influence the accuracy of model-based patient selection for proton therapy. A reduction of NTCP-model uncertainty is necessary to reach more accurate model-based patient selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…Bijman et al assessed the model uncertainty using a probability distribution (mean and CI) of the model coefficients from multivariable NTCP models in head and neck cancers and concluded that the accuracy of the MBA on patient selection for PBT is largely affected by the uncertainty in the NTCP models [ 4 ]. In contrast, the uncertainty of the LKB NTCP model for RILD relies on the model parameters’ variability, and .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bijman et al assessed the model uncertainty using a probability distribution (mean and CI) of the model coefficients from multivariable NTCP models in head and neck cancers and concluded that the accuracy of the MBA on patient selection for PBT is largely affected by the uncertainty in the NTCP models [ 4 ]. In contrast, the uncertainty of the LKB NTCP model for RILD relies on the model parameters’ variability, and .…”
Section: Discussionmentioning
confidence: 99%
“…The selective use of PBT relies on a predefined ∆NTCP threshold, such as 10% for Grade II or 15% for total clinical benefit, according to the Dutch Society of Radiation Oncology (NRVO) guidelines [ 3 ]. However, these models were derived from a statistical assumption based on a small subset of the population, and the model uncertainty affects the accuracy of PBT selection [ 4 ]. In other words, underestimating ∆NTCP can eliminate the opportunity to benefit from PBT, whereas an overly cautious practice might cause the unnecessary use of this high-cost treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, proton treatment planning studies which draw upon empirical RBE models are increasingly highlighting end-of-range RBE effects as a serious area for concern with regards to possible toxicities, 38 and RBE uncertainties clearly impact upon both normal tissue complication probability and tumour control probability estimates for proton therapy. 39 Improved understanding of proton RBE would bring increased precision to model-based selection of those patients who stand to benefit most from proton therapy, 40 enhancing clinical trial design and interpretation. With sufficient validation, multiscale RBE models could also offer true "biological dose" optimisation within clinical treatment planning systems, dose-painting of radioresistant tumour regions and perhaps, even treatment individualisation based upon a specific patient's tumour or normal tissue biology.…”
Section: The Potential Impact Of Multiscale Rbe Modelling On Clinicalmentioning
confidence: 99%
“…Due to the effect of dose uncertainties on the accuracy of model-based patient selection [ 17 ], the treatment plan robustness and differences between planned and delivered dose distributions need to be investigated. The accuracy of the beam delivery requires reliable beam profiles and minimal uncertainties in beam range and set-up errors.…”
Section: Proposed Systematic Development Of Tcp/ntcp Modelsmentioning
confidence: 99%
“…However, some statistical issues remain unresolved: for example, studies on NTCP models did not consider model uncertainties. This could lead to random errors and misinterpretations of the results [ 17 ]. Additionally, appropriate thresholds must be defined at specific endpoints for each particular tumor on a cost–effectiveness basis.…”
Section: Opinions Identifying the Shortcomings Of A Model-based Appromentioning
confidence: 99%